« Mourir dans un baiser » Un archétype du féminicide ? - Jacqueline Carroy; Marc Renneville (Criminocorpus)
Feminicide, defined as the killing of a woman because of her sex, is a word recently coined to designate a social act that is less and less tolerated in our societies. This act was largely confused, particularly in the 19th century, with the vast nebula of "crimes of passion", murders committed under the influence of a passion for love exacerbated by jealousy or the impossibility of uniting with the loved one. There is, however, another way in which love leads to death, and that is the double suicide of lovers. When the man survives the death of his partner, the intentionality of the gesture raises questions. We analyse this on the basis of a double suicide committed in Constantine, Algeria, on 25 January 1888. This case, which was very quickly made into a "cause célèbre", also raises questions about the status of the murderer, Henri Chambige. Was he an overly sensitive and imaginative idealist, lost in his readings of Sand, Stendhal, Balzac and Vigny? Or was he simply a cynic who hated the woman who denied him the love he expected? As for the female victim, can she be guilty of betraying her husband? And of having preferred death to dishonour? Paul Bourget wrote Le Disciple in the wake of this crime, a great critical and bookstore success, to resolve the moral question of the influence of literature and the new theories of psychology on youth. Anatole France and Maurice Barrès also took a stand. The Chambige affair has a unique place in the history of feminicide in literature. It gave rise to committed and sometimes violent positions, revealing a criminal imagination that did not think of itself as such, but it also provoked reactions against the killing of women, thus initiating a first movement of social awareness of what was not yet known as feminicide.